The Influence of Slow Fashion Attributes on Purchase Intention and Willingness to Pay Price Premium For Slow Fashion Products on Online Platform (Journal of Innovation, Business and Entrepreneurship, 2020)
The growing number of internet users has resulted in users consuming digital media. However, the slow fashion industry in Indonesia still does not have the maximum opportunity to market their products via the internet, even though by looking at the quality of the products, they can compete in a broader market. Lack of information about products and differentiation between slow fashion products and fast fashion is also why there are still many consumers who are not interested in buying slow fashion products, especially at a premium price. In the slow fashion industry itself, there are differentiate several attributes between slow fashion and fast fashion. The lack of recognition of Indonesia's slow fashion products from the consumers' perspective is the main focus of this research. This study aims to determine the contribution of slow fashion attributes on purchase intentions and customers' willingness to pay premium prices for slow fashion products through online platforms, mainly to assist SelectedGoods in developing strategies in finding brand merchants that accordance with the values of slow fashion and also slow fashion consumer values. This study adopted a framework established by Jin & Jung in 2014. This research has five primary constructs regarding the attributes in a slow fashion that affect purchase intentions and customers' willingness to pay premium prices for slow fashion products through online platforms. This study uses PLS-SEM as a data processing technique to analyze the relationship between the attributes of slow fashion (fairness, Authenticity, functionality, localism, and exclusivity), customer perceptions, purchase intensity, and customer willingness to pay premium prices for slow fashion products through online platform. This study resulted in 244 slow fashion consumers aged 18-35 in Bandung and Jakarta. The study results indicate that all items, directly and indirectly, affect the purchase intensity and the willingness of customers to pay premium prices for slow fashion products through online platforms. Fairness is the attribute with the highest score that directly affects the two dependent variables. Localism is the attribute with the lowest score but has a significant positive value directly in influencing the two dependent variables. These findings are expected to help SelectedGood understand the slow fashion attributes from slow fashion customer perceptions and gain insight into the right strategy for choosing brand merchants.Keywords: slow fashion, slow fashion attributes, purchase intension, price premium, SEM-PLS